1976
DOI: 10.1128/jb.128.2.598-603.1976
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of hypoxanthine transport in Neurospora crassa

Abstract: Hypoxanthine uptake and hypoxanthine phosphoribosyltransferase activity (EC 2.4.2.8) were determined in germinated conidia from the adenine auxotrophic strains ad-1 and ad-8 and the double mutant strain ad-1 ad-8. The mutant strain ad-1 appears to lack aminoimidazolecarboximide ribonucleotide formyltransferase (EC 2.1.2.3) or inosine 5'monophosphate cyclohydrolase (EC 3.5.1.10) activities, or both, whereas the ad-8 strain lacks adenylosuccinate synthase activity (EC 6.3.4.4). Normal (or wild-type) hypoxanthine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

1977
1977
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…4. As seen in the figure, the ad-8 strain could not accumulate hypoxanthine at all from the medium, which is in agreement with earlier reports (6,15), whereas the ad-4 strain had lowered ability, compared with the wild type. In general, even in the wild type the rate of hypoxanthine accumulation through the general transport system was lower than that of adenine accumulation, which may be a reflection of the differences in the affinity of this system for the two purine bases.…”
Section: Results |supporting
confidence: 92%
See 2 more Smart Citations
“…4. As seen in the figure, the ad-8 strain could not accumulate hypoxanthine at all from the medium, which is in agreement with earlier reports (6,15), whereas the ad-4 strain had lowered ability, compared with the wild type. In general, even in the wild type the rate of hypoxanthine accumulation through the general transport system was lower than that of adenine accumulation, which may be a reflection of the differences in the affinity of this system for the two purine bases.…”
Section: Results |supporting
confidence: 92%
“…6). Considering previous reports that growth in ammoniumcontaining medium stimulated hypoxanthine transport (i.e., the general purine system) in Neurospora (15,16), the present finding may suggest that ammonium is also required for the expression of the adenine-specific system. The possibility, however, that the formation of the second system is linked to the germination process cannot be ruled out.…”
Section: Results |supporting
confidence: 73%
See 1 more Smart Citation
“…It is posible that the reduction of HPRTase activity in these strains is simlar to that observed in ad-8 mutants of Neurospora. The primary leon of the ad-8 mutant is the loss of activity of adenylosuccinate synthetase (22), but the mutants also posess a defective general purine permease and HPRTase (29). It seems that in the present case the reduction in the level of HPRTase activity in the 6-methylpurine-resistant mutants is consequent to the defect that led to the 6methylpurine resistance rather than the cause of it.…”
Section: Discussionmentioning
confidence: 66%
“…In our experience, even short-term pulse-labeling studies of purine bases always yielded purine nucleotides in subsequent extractions of the cells (24,25). Sabina et al (29) found that an adenine-requiring mutant ofNeurospora (ad-8) not only could not transport hypoxanthine, but its hypoxanthine PRTase (EC 2.4.2.8; HPRTase) activity was very low. The last two observations could mean either that a group tranalocation process is operative in Neurospora for purine bases or that purine bases are metabolized to nucleotide form very rapidly upon entry into the cells and that both transport and phosphoribosylation may be regulated by the same intracellular accumulation products.…”
mentioning
confidence: 76%